Synthesis and liquid phase sintering of TiN/TiB2/Fe-Cr-Ni nanocomposite powder - Kim, Ji Woo; Chung, Hee-Suk; Shim, Jae-Hyeok; Ahn, Jae-Pyoung; Cho, Young Whan; Oh, Kyu Hwan (ELSEVIER SCIENCE SA, 2006)
Nanostructured TiN/TiB2/Fe-Cr-Ni composite powder has been prepared via high energy ball milling. Ti and BN powders are reacted to form a uniform mixture of TiN and TiB2 within 2 h of milling by a mechanically activated self-sustaining reaction (MSR). The crystallite sizes of TiN and TiB2 are about 7 and 16 nm, respectively, after 32 h of milling. Through liquid phase sintering and optimizing the milling time, a compact body with almost full density could be obtained which has a narrow grain size distribution and exceptionally high hardness. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: BN